2011
DOI: 10.1371/journal.pone.0020354
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in Superoxide Dismutase 1 Causes Oxidative Stress and p38 MAPK Activation Following RVFV Infection

Abstract: Rift Valley fever (RVF) is a zoonotic disease caused by Rift Valley fever virus (RVFV). RVFV is a category A pathogen that belongs to the genus Phlebovirus, family Bunyaviridae. Understanding early host events to an infectious exposure to RVFV will be of significant use in the development of effective therapeutics that not only control pathogen multiplication, but also contribute to cell survival. In this study, we have carried out infections of human cells with a vaccine strain (MP12) and virulent strain (ZH5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…Our earlier reverse-phase protein microarray (RPMA) studies reveal that infection of human small airway lung epithelial cells (HSAECs) by the virulent ZH501 strain of RVFV elicit multiple host phospho-signaling events relevant to diverse pathological manifestations such as oxidative stress, activation of stress response MAPKs, and DNA damage (17,18). Multiple * This work was supported by United States Department of Energy Grant ongoing follow-up studies indicate that the signaling responses detected in HSAECs is also observed in many other cell types such as HepG2 cells, HeLa cells, and 293T cells following RVFV infection (Refs.…”
Section: Rift Valley Fever Virus (Rvfv)mentioning
confidence: 99%
“…Our earlier reverse-phase protein microarray (RPMA) studies reveal that infection of human small airway lung epithelial cells (HSAECs) by the virulent ZH501 strain of RVFV elicit multiple host phospho-signaling events relevant to diverse pathological manifestations such as oxidative stress, activation of stress response MAPKs, and DNA damage (17,18). Multiple * This work was supported by United States Department of Energy Grant ongoing follow-up studies indicate that the signaling responses detected in HSAECs is also observed in many other cell types such as HepG2 cells, HeLa cells, and 293T cells following RVFV infection (Refs.…”
Section: Rift Valley Fever Virus (Rvfv)mentioning
confidence: 99%
“…[17][18][19][20]24,28 ROS and malfunctioning mitochondria are important contributors to apoptosis in these infected cells. We hypothesized that VEEV infection would disrupt mitochondrial function which would contribute to apoptosis.…”
Section: Veev Infection Results In Loss Of Mitochondrial Membrane Potmentioning
confidence: 99%
“…U87MG cells are readily infected by VEEV and display robust viral replication kinetics. [6][7][8][28][29][30] U87MG cells were infected with the TC-83 strain of VEEV at increasing multiplicities of infection (MOIs). Changes in mitochondrial membrane potential were quantified by labeling active mitochondria with TMRE reagent (TetraMethyl Rhodamine, Ethyl ester).…”
Section: Veev Infection Results In Loss Of Mitochondrial Membrane Potmentioning
confidence: 99%
“…Ermler et al (2014) showed that NSs deletion mutants cause mouse bone marrow derived macrophages (BMDM) to produce greater amounts of IFN-a when compared with the attenuated vaccine strain MP-12, which encodes an intact NSs protein. Narayanan et al (2011) found that infection with RVFV vaccine strain MP-12 or pathogenic strain ZH501 resulted in increased TNF-a in primary human small airway lung epithelial cells. These data support the notion of cell type specific responses to RVFV infection.…”
Section: Introductionmentioning
confidence: 95%